Evaluation of california mastitis test (cmt) for diagnosis of subclinical mastitis in hair goats - İbrahim Aydın; H. Hüseyin Hadimli; H. Ahmet Çelik; Zafer Sayın (Eurasian Journal of Veterinary Sciences)
The objective of this study is to evaluate of CMT for diagnosis of subclinical mastitis in Hair goat, Konya and to isolate bacteria causing subclinical maslitis. For this purpose, 508 goali were examined from five herds. Milk samples were collected from 985 mammary giands and checked by CMT. All CMT positive milk samples and a number of 50 negative milk samples (as a control) were used for microbiological analyses. According to CMT results, 11.7% of goats and 7,9% of mammary glands were classified to htve subclinical mastitis. While 32.2% of the infections were bilateral, 67.8% were unilateral. Infections were detected in a ratio of 43.6% in the right glands and 56,4% in the left glands, and there was no statistical difference (P > 0.05). Among the CMT positive milk samples. 79.5% had bacterial growth, whereas no bacteria were detected in 20.5%. Of the CMT negative milk samples, only 14% showed bacterial growth while 86% were free of growth. By comparison cultural results with CMT from samples obtained from subclinical cases, CMT were verified by bacterial growth (P > 0.05). The mostly detectod pathogen in CMT positive milk samples was Coagulaz negative Staphylococci <CNS) with a 69.3% prevalence. The other pathogens those were isolated Staphylococcus aureus (%17.7), Corynebacterium spp. (%4.8), Streptococcus spp. (%3.2), Escherichia coli(%3.2) and Yeasts (%1.6). As a result, CMT can detect subclinical^ infected and uninfected mammary glands with a good accuracy when 0 and +1 were considered negative and +2 and +3 were positive in hair goats. Therefore, CMT can be recommended for detection of subclinical mastitis since it is fast, easy and cost-effective.